rozwiaz rownanie
1) (x- √2)(x +2√2) = x² +1
2) 2 - √2x + x- 4
3) (x+2√2) √2 = √3x -1
4) 1 + √3x = x+2
5) (x + √3)(2 +√3) =4 +2√3
6) (x + √5)(1 + √5) = √5



Odpowiedź :

1) (x- √2)(x +2√2) = x² +1
x²+2√2x-√2x-4=x²+1
x²+√2x-4-x²-1=0
√2x-5=0
√2x=5//:√2
x=5/√2

2) 2 - √2x + x- 4=0
√2x+x-2=0
√2x+x=2
x(√2+1)=2//:(√2+1)
x=2/(√2+1)

3) (x+2√2) √2 = √3x -1
√2x+4=√3-1
√2x=√3-1-4
√2x=√3-5//:√2
x=(√3-5)/√2

4) 1 + √3x = x+2
√3x-x=2-1
√3x-x=1
x(√3-1)=1//:(√3-1)
x=1/(√3-1)

5) (x + √3)(2 +√3) =4 +2√3
2x+√3x+√6+3=4+2√3
2x+√3x=4+2√3-√6-3
x(2+√3)=1+2√3-√6//:(2+√3)
x=(1+2√3-√6)/(2+√3)

6) (x + √5)(1 + √5) = √5
x+√5x+√5+5= √5
x+√5x=√5-√5-5
x (1+√5)=-5
x=-5/(1+√5)
1) x²+2√2x-√2x-4= x²+1
√2x=5
x=5√2/2
2) 2 - √2x + x=4
x(1-√2)=4-2
x=2/1-√2 pozbywamy się niewymierności mnożąc licznik i mianownik przez 1+√2
x=-2-2√2
3)(x+2√2) √2 = √3x -1
√2x+4- √3x =-1
x(√2- √3)=-5
x=-5/√2- √3 pozbywamy się niewymierności mnożąc przez √2+ √3
x=5√2+5√3
4)1 + √3x = x+2
√3x-x=1
x(√3-1)=1
x=1/√3-1
x=√3+1/2
5) (x + √3)(2 +√3) =4 +2√3
2x+√3x+2√3+3=4+2√3
x(2+√3)=1
x=1/2+√3
x=2-√3
6)(x + √5)(1 + √5) = √5
x+√5x+√5+5=√5
x(1+√5)=-5
x=-5/1+√5
x=5-5√5/4